Gestão democrática e participativa: um estudo do Instituto Federal da Paraíba/Campus João Pessoa, a partir do período de redemocratização do Estado brasileiro - Nogueira, Cleoneilton Lopes (2020)
The theme of this prep threads about the democratic-participative management in higher education. Its study approach is the democratic participation of the academic community on the management and planning of the Federal Institute of Paraíba (IFPB) from the João Pessoa Campus, starting from Brazil’s political redemocratization period, when the organized academic community puts in check the social participation proposes on the management of the institute. Our objective is to analyse the participative process from the academic community as a motion for the effectuation of IFPB - João Pessoa Campus’ democratic management. The theoretical reference for the analysis addressed three fundamental categories that are needed for the study’s enlightenment and contextualization on the society’s historic process and on the brazilian’s political lifespan. Thus far, it was sought to gather the perception from the managers and the academic community, as well as the established conditions and standards of participation. The theoretical-methodological perspective adopted is sustained in the dialectic method, which seeks to understand the relations and concrete actions from the involved fractions of the institutional management of the IFPB - João Pessoa Campus. This prep is characterized by its qualitative nature, combining two complementary kinds of methodological procedures: the documental analysis of the institution and the field research through interviews. They followed two semi-structured scripts and were applied to two interviewee profiles: members from the academic community (teachers, administrative technician and students) and institutional managers. The acquired results showed that the participative process is recognized by the managers and the community as fundamental for the institutional democratic lifespan’s set up. IFPB has legitimate spaces in the institution’s regulatory order, like the managing council and the collegiate. The participative process had its peak until 2015. On this period was arised a statuary that was made with all the institution’s segments participating effectively. Then, there was a dousing process, which made the community leave the consultative collegiate spaces in a deliberative way, spaces that the community has a guaranteed seat and decisive power. Even though the managers recognize the importance and legitimacy that are resultants from the participative process, not always perform greater efforts on the mobilization of the academic community. With this analysis, we can conclude that are structural conditions for the participative process, which were resulted from the previous dynamic participation. Although, the community is not as motivated as before to reproduce this dynamic democratic participation in the IFPB’s academic lifespan at the current conjunctural moment.